Blockchain Based Identity Management System - Gobika S.; Vaishnavi N. (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Traditional identity management systems often suffer from security vulnerabilities, data breaches, and inefficiencies due to centralized control. Blockchain technology offers a decentralized and tamper-resistant alternative for identity management, enhancing security, privacy, and user control. This paper explores a blockchain-based identity management system that leverages decentralized identifiers (DIDs) and verifiable credentials to provide a secure, transparent, and user-centric identity framework. The proposed system ensures data integrity, minimizes identity fraud, and enables seamless authentication across multiple platforms without reliance on a central authority. Additionally, smart contracts facilitate automated verification processes, improving efficiency and reducing the risk of unauthorized access. The study also discusses the potential challenges, such as scalability and regulatory compliance, and proposes solutions to enhance the adoption of blockchain-based identity systems.